Strategi Guru Dalam Menjalankan Kegiatan Pembelajaran Di Masa Pandemi - Detania Hidapenta; Hana Nurur Rohmah; Juliantika Juliantika; Husen Windayana (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2022)
The purpose of this paper is to describe the teacher's strategy in carrying out learning activities during the pandemic. The methodology or approach used in this paper uses a literature review method, while data collection is carried out by reviewing several journals and books. Until later the results of this data collection can be concluded that in online learning the teacher must have special strategies related to technology so that in its implementation it is in accordance with learning objectives that are in line with the applicable curriculum. In this case the author found a suitable learning strategy, namely a multiplatform learning strategy. This strategy makes it easier for students in learning because students can access applications anywhere and anytime. So that learning can continue effectively.